2018
DOI: 10.1038/s41562-018-0343-2
|View full text |Cite|
|
Sign up to set email alerts
|

Social learning strategies for matters of taste

Abstract: Most choices people make are about "matters of taste" on which there is no universal, objective truth. Nevertheless, people can learn from the experiences of individuals with similar tastes who have already evaluated the available options-a potential harnessed by recommender systems. We mapped recommender system algorithms to models of human judgment and decision making about "matters of fact" and recast the latter as social learning strategies for "matters of taste." Using computer simulations on a large-scal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 89 publications
2
21
0
Order By: Relevance
“…In a pathbreaking experimental study, Salganik et al (2006) found that information on other listener's musical preferences results in an amplified inequality of popularity when compared to a world of independent listeners. Using social cues in the form of aggregated information might be beneficial for individuals in cultural markets in which preference is a matter of taste, but there are multiple strategies to leverage such information and its fit varies between individuals (Analytis et al, 2018). In the case of artists, during their careers, "small differences in talent become magnified in larger earning differences" (Rosen, 1981).…”
Section: Research Backgroundmentioning
confidence: 99%
“…In a pathbreaking experimental study, Salganik et al (2006) found that information on other listener's musical preferences results in an amplified inequality of popularity when compared to a world of independent listeners. Using social cues in the form of aggregated information might be beneficial for individuals in cultural markets in which preference is a matter of taste, but there are multiple strategies to leverage such information and its fit varies between individuals (Analytis et al, 2018). In the case of artists, during their careers, "small differences in talent become magnified in larger earning differences" (Rosen, 1981).…”
Section: Research Backgroundmentioning
confidence: 99%
“…In contrast to these previous works, in many daily choices under social influence, one generally considers not only one, but several sources of social information, and these sources are rarely chosen randomly [ 41 ]. Even when not actively selecting information sources, one routinely experiences recommended content (e.g., books on Amazon, movies on Netflix, or videos on YouTube) generated by algorithms which incorporate our ‘‘tastes’’ (i.e., previous choices) and that of (similar) others [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…collaborative filtering algorithms (Das et al 2007;Koren and Bell 2015;Ricci, Rokach, and Shapira 2011). Recently, researchers have shown that individual social influence can be affected by an individual's position in the population distribution and similarity with others (Pipergias Analytis et al 2020;Analytis, Barkoczi, and Herzog 2018). Similar findings may thus be observed on more realistic content recommendation algorithms.…”
Section: Discussionmentioning
confidence: 84%